A Case of Follicular Tumor of Uncertain Malignant Potential (FT-UMP) with Glomeruloid Features Showing Capsular Mucinous Degeneration. (11th March 2021) - Cabibi, Daniela; Mondello, Andrea; Florena, Ada Maria; Rimi, Giulia; Giannone, Antonino Giulio; Cipolla, Calogero; Valerio, Maria Rosaria; Graceffa, Giuseppa
Abstract : The most recent revision of the World Health Organization (WHO) Classification of Tumours of Endocrine Organs introduced a new variant of follicular thyroid carcinoma (FTC). It is characterized by a "glomeruloid" architectural pattern of growth. We present a case of follicular tumor with glomeruloid features, with Alcian Blue positive mucinous stromal degeneration in foci of questionable capsular microinvasion. At our knowledge, this the second case of glomeruloid follicular tumor in the literature and the first case in which Alcian Blue staining was used to investigate capsular invasion. Moreover, RAS mutation further supports that this is a variant of follicular tumor with uncertain malignant potential.